(untitled) (Islamic Sciences Journal, 2023)
There are many studies that dealt with the Holy Qur’an starting from the Ist century A.H. till the present day. Throughout this study of the commentary of Al Jawahir Al Hisan bu Abu Zaid Al Tha’aliby (decd. 875 A.H.), and my tackling many issnes concerning the reasons of Qur’anic expressions, I noticed some topics that came in this blessed interpretation which is considered one of the important commentaries as well as an important reference of language as it carries various inclinations such as the influential, the linguistic and the stylistic inclinations. Therefore, I decided, among many options, to choose the study of structures. Hence, this research includs four topics; first: reasons of preference in sentences, second: reasons of preferences in Qur’anic citations, third: reasons of preferences in parsing and fourth: reasons of preferences in starting and stopping.